Two-Dimensional Numerical Study of Two Slot Jets Impinging On Flat Surfaces at Various Angles - MOHD ZAHIDIN, MUAZ; md seri, suzairin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Jet impingement cooling systems are currently utilised in many sectors. In order to develop a more effective jet impingement cooling system, numerous ways were examined. This thesis investigates the effect of nozzle angle on jet impingement in order to determine a heat transfer relationship. This research also investigate the spacing distance between nozzle’s edge to the impingement surface and Reynolds number at various angle. These investigations are required in addition to the current research efforts for future cooling system development in global industries. Three primary factors were varied in the experiment such as the nozzle angle (30°, 60°, and 90°), the ratio distance between the nozzle’s edge and the impinge surface to the width of the nozzle (r/B= 5, 8, and 16) and the Reynolds number (Re= 500, 1000,2000,10000 and 20000). The heat source are heated at 336K or 62.85 ⁰C and cooled down by the flow of air from the nozzle. The heat source temperature after cooling are measured and collected. The result discovers about the relationship nozzle angle for jet impingement which is heat transfer are more efficient when the angle of nozzle approaching to the normal line compare to the lower angles of the nozzle. In addition, a high heat transfer is produced by a high Reynolds number and the heat transfer shows decrease in rate when the r/B or the ratio distance between the nozzle’s edge and the impinge surface to the width of the nozzle increase, implying that the systems will be cooled effectively when the nozzle is near to the target surface.